Implementasi Hiradc dalam Upaya Mencegah Kecelakaan Kerja pada Pembangunan Gudang Polygon oleh PT. X - Nadhifa Setyo Ayu Mustikaning Hapsari; Ratna Ayu Ratriwardhani (University of Nahdlatul Ulama Pasuruan, 2021)
As aneffort to prevent work accidents, companies need to implement a risk management that can be appliedthrough Hazard Identification Risk. Assessment and Determining Controls (HIRADC) contained in ISO45001: 2018. This research was conducted with the aim of knowing the suitability of the application ofHIRADC in polygon warehouse construction with ISO 45001: 2018 clause 6.1.2 “Hazard Identificationand Assessment of Risks and Opportunities”. The type of research used is descriptive with data collectionthrough direct observation to the field and interviews with several workers. Based on observations in thefield, the impact of potential hazards and risks can have a direct impact on workers. The controls appliedtend to be in terms of administration and use of PPE. Broadly speaking, the controls that have beenimplemented by PT.X are carried out effectively so that the implementation of HIRADC is in accordancewithISO45001:2018clause 6.1.2